COMPANY SIZE STRENGTHENS THE INFUENCE OF ASSET STRUCTURE AND CAPITAL STRUCTURE ON FIRM VALUE - Wahyu, Supami; Mardiana, Mardiana (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This study discusses the size of the firm that is approved by the asset structure and capital structure of firm value. This research is a quantitative study. The analysis technique used is Multiple Regression Analysis (MRA). The results of this study find facts about firm that manage the relationship of assets and capital structure to the value of the firm. Partially, the size of the company increases the asset structure against the value of the firm. The size of the firm is not in accordance with the firm structure of firm value. In conclusion, the size of the firm increases the use of assets in increasing the value of the firm.